Investigation into The Uses and Practices of Continuous Assessment Among Secondary School Teachers in Biu Educational Zone of Borno StateInvestigation into The Uses and Practices of Continuous Assessment Among Secondary School Teachers in Biu Educationa - Zakka, Kaku,; W. Waba, Williams, (Kashere Journal of Education, 2021)
This research assess uses and practice of continuous assessment among senior secondary school teachers in Biu Educational Zone of Borno State, Nigeria. Descriptive survey design was employed, all the one hundred and ninety-two (192) teachers in the zone constitute the population and sample of the study. Three objective, one hypotheses were formulated to guide the study, questionnaire was used. Frequency and percentage were used to answer the research questions. While one-way analysis of variance (ANOVA) were used to answer the hypotheses at 0.05 level of significance data collected was statistically analyzed using statically package of social science (SPSS) at 0.05 level of significance. The major findings of the study revealed that: teachers do not make used of continuous assessment in decision making, there is no significant in the practice of continuous assessment among less qualified, qualified and unqualified teachers. The researchers recommended that: the state government as well as stake holders in Biu Educational Zone of Borno state should only recruit teachers with educational background, those that are still in the system should encouraged to have post graduate diploma in education. Administrator and stakeholders should from time to time organize in house workshop or seminars for teachers in order to acquire real knowledge of C.A. Government should also provide appropriate continuous assessment guideline to help teachers on how to conduct and use continuous assessment, also regular supervision should be done to ensure the effective and efficient use of continuous assessment.